Sociodemographic and behavioural correlates of lifetime number of sexual partners: findings from the English Longitudinal Study of Ageing - Jackson, Sarah E (BMJ Sex Reprod Health, 2019)
BACKGROUND: No current data are available on correlates of lifetime sexual partners at older ages. This study aimed to explore correlates of the lifetime number of sexual partners in a sample of older adults. METHOD: Data were from 3054 men and 3867 women aged ≥50 years participating in the English Longitudinal Study of Ageing. Participants reported their lifetime number of sexual partners and a range of sociodemographic characteristics and health behaviours. Multivariable multinomial logistic regression was used to examine correlates of lifetime number of sexual partners, with analyses performed separately for men and women and weighted for non-response. RESULTS: Younger age, being separated/divorced or single/never married, being a current or former smoker, and drinking alcohol regularly or frequently were independently associated with a higher number of sexual partners in both men and women. Homosexuality in men and bisexuality in women were also associated with a higher number of sexual partners. White ethnicity, regular moderate and vigorous physical activity, and the absence of limiting long-standing illness were independently associated with a higher number of sexual partners in women only, and being in the highest and lowest quintiles of wealth was independently associated with a higher number of sexual partners in men only. CONCLUSIONS: A higher lifetime number of sexual partners is associated with a number of sociodemographic and behavioural factors. An understanding of who is more likely to have had more sexual partners may help health practitioners to identify individuals who are at greatest risk of sexually transmitted infection and their associated health complications across the life course.